Meningkatkan ketuntasan belajar siswa dengan model pembelajaran introduction, connection, aplication, reflection dan extension Kelas VIII dalam tema narrative text pola dakwah Nabi Muhammad SAW. di Madinah mata pelajaran SKI di MTs Negeri Krian Sidoarjo - Nawawi, Syu'aib (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
One of the learning models that includes a series of planned learning experiences arranged in a systematic, operational, and directed way to help students master specific learning objectives is an ICARE learning tool. The objectives of this research are: 1) To compile the learning model of Intellection, connection, aplication, reflection, extension of Class VIII in theme "narrative text of propagation pattern of Prophet Muhammad SAW. In Medina "subjects History of Islamic Culture in MTs Negeri Krian Sidoarjo 2) To analyze the learning model of ICARE (Introduction, connection, aplication, reflection, extension) can improve the learning completeness of Class VIII in theme" narrative text propagation pattern of Prophet Muhammad SAW. In Medina "subjects History of Islamic Culture in MTs Negeri Krian Sidoarjo ?. From the results of this research development can be concluded: 1) ICARE learning device products reviewed from students in MTs Negeri Krian Sidoarjo Fair enough, with a score of 3.53, (enough), from peer assessment no less than 3.0., With qualifications 4.15 (Good), no expert assessment of less than 3.0., With qualification 4.15 (Good) 2) ICARE learning tool product can improve student learning outcomes in MTs Negeri Krian Sidoarjo, from trial class experience improvement in mastery with average value Average Pre test 81.25 increased at the test post 88.13 while the percentage of pre-test completeness was 71.88% increased to 96.88%.